SKELETON ANALYSIS OF THE CRANII REGION IN THE CASE OF DOLPHINS (Tursiops trucantus) STRANDED ON SENGGIGI BEACH WEST LOMBOK REGENCY - Rahmawati, Septyana Eka; Munawaroh, Muhammad; Barmawi, Muhammad; Kholik; Riwu, Katty Hedriana Priscilia; wijaya, I Gusti Made Arjana (Universitas Airlangga, 2024)
Cetaceans are a group of marine mammals fully adapted to aquatic life including whales and dolphins. Dolphins belong to a group of marine animals known as Cetaceans that have evolved completely to live in water. In Indonesian waters, almost all cetacean species have been classified as protected biota. Many cetacean deaths have been linked to water pollution and underwater seismic activity. The bottlenose dolphin (genus Tursiop) is one of the most studied cetacean species due to its wide distribution in tropical and temperate waters and its friendly behavior towards humans. This research shows that the results of the size of the Tursiops truncatus bones in the Cranii section found on Senggigi Beach are different from the results of the size of the Cranii bones of Tursiops truncatus found on Korea's Jeju Island. In a review of literature written about the bones of the Tursiops truncatus species from Korea, Jeju Island. Each part of the Os Cranii on Tursiop truncatus found on Jeju Island, Korea has a very different size from the Tursiop truncatus found on Senggigi Beach which can be concluded that the size of the Os Cranii on Tursiops truncatus found on Jeju Island, Korea has the same size. larger than the size of Tursiops truncatus found on Senggigi Beach, West Lombok Regency. The cause of differences in bone size could be due to diet and habitat. A study on stable isotope analysis of marine mammals off the coast of Northwest Africa and unique trophic niches says mammalian bones reflect not only differences in trophic level but also shifts in foraging areas.